Assessment of Prospective Physics Teachers’ Energy Literacy: A Recent Approach - Muhamad Yusup; Agus Setiawan; Nuryani Y. Rustaman; Ida Kaniawati (Newest Updates in Physical Science Research Vol. 9, 2021)
Energy literacy is one of the keys to addressing the energy problems in the world today, along with efforts to develop green energy technologies. We need to know how energy-literate the citizens are. Measuring literacy energy among prospective physics teachers is essential because they are the next generation of educators responsible for this problem. Nevertheless, there is no assessment instrument to measure how literate they are. This study aims to develop a framework for the assessment of the prospective physics’ teacher. Sample of items developed based on the framework also included in this article.